(untitled) (Sustainability in Debate, 2021)
The concept of green innovation refers to innovation that seeks to make radical or progressive improvements to products or processes that contribute to sustainable development. Green innovation can improve the global image of a business and lead to better market performance. Green innovation projects can contribute to economic growth and a positive quality of life without negatively affecting the environment. Consequently, this study aims to examine the relationship between the development of green materials resulting from green innovation and project management. To achieve the research objective, we conducted a multi-case study with companies developing green innovation derived textile. The findings show that the firms surveyed do not use formal project management to execute their green innovation projects and that their project management is intuitive. Although the companies surveyed are concerned with sustainable development and strive to innovate to satisfy their customers responsibly, their project management practices are informal. This study contributes to the practice. It is possible to introduce project management into enterprises to enhance green innovation while adapting practices or using less formal and bureaucratic techniques.